Engaging audiences: A critical reflection on the Kaba Festival 2014-2024, West Sumatera - Khusairi, Abdullah; Nurhayati, Meysanda (Islamic Communication Journal, 2025)
Effective communication is a key factor in the development of arts and culture, especially in traditional festivals involving community participation. This article explores the Kaba Festival organized by Nan Jombang Dance Company, founded by Indonesian dance maestro Ery Mefri. Using a critical reflection approach, the study analyzes communication dynamics in the festival by observing the participation and appreciation of artists, cultural figures, and academics. Findings show that participatory and community-based communication strategies enhance audience and participant engagement. Despite limited human resources, the festival successfully strengthens Nan Jombang’s reputation, evolving from modest beginnings into a nationally and internationally recognized cultural platform. Now entering its 40th year, Nan Jombang’s experience forms the basis for a strategic five-year plan (2025–2030) focused on cross-sector collaboration, digital media optimization, and training in cultural journalism. The study offers a model for building a sustainable, globally relevant art ecosystem while preserving local traditions. ***** Komunikasi efektif menjadi salah satu kunci dalam pengembangan seni dan budaya, terutama dalam konteks festival tradisional yang melibatkan partisipasi elemen masyarakat. Artikel ini bertujuan mengeksplorasi penyelenggaraan Kaba Festival oleh Nan Jombang Dance Company, yang didirikan Maestro Tari Indonesia, Ery Mefri. Melalui pendekatan refleksi kritis, artikel ini menganalisis dinamika komunikasi dalam perjalanan Kaba Festival dengan meneliti partisipasi, dan apresiasi para seniman, sastrawan, budayawan hingga akademisi. Hasil penelitian menunjukkan, penggunaan strategi komunikasi partisipatif dan berbasis komunitas meningkatkan keterlibatan kehadiran peserta dan penonton. Efektivitas yang tinggi dengan keterbatasan human resource, telah mengantarkan Kaba Festival dalam posisi puncak eksistensi sebagai sebuah kegiatan seni menggerek nama Nan Jombang Dance; tumbuh dari keterbatasan dan terus berkembang tanpa batas. Nan Jombang berkembang sebagai platform kebudayaaan yang sangat diperhitungkan di kancah nasional dan internasional hingga berusia 40 tahun. Temuan ini menjadi dasar perumusan program strategis lima tahun (2025-2030) Kaba Festival yang mencakup penguatan kolaborasi lintas sektor, penggunaan media digital secara optimal dan pelatihan jurnalisme seni-budaya bagi pelaku seni dan jurnalis. Hasil penelitian bisa menjadi contoh dasar tumbuhnya ekosistem seni yang berkelanjutan dan relevan dengan dinamika global, sekaligus menjaga kekayaan tradisi lokal.